Anti-biofilm Approach in Infective Endocarditis Exposes New Treatment Strategies for Improved Outcome - Lerche, Christian Johann; Schwartz, Franziska; Theut, Marie; Fosbøl, Emil Loldrup; Iversen, Kasper; Bundgaard, Henning; Høiby, Niels; Moser, Claus (Frontiers in Cell and Developmental Biology, 2021)
Infective endocarditis (IE) is a life-threatening infective disease with increasing incidence worldwide. From early on of the antibiotic era it was recognized that high dose and long-term antibiotic therapy was correlated to improved outcome. In addition, for several of the common microbial IE etiologies, use of combination antibiotic therapy further improves outcome. IE vegetations on affected heart valves from patients and experimental animal models resemble biofilm infections. Besides the recalcitrant nature of IE, the microorganisms often present in an aggregated form and gradients of bacterial activity in the vegetations can be observed. Even after appropriate antibiotic therapy, such microbial formations can often be identified in surgically removed, infected heart valves. Therefore, persistent or recurrent cases of IE after apparent initial infection control can be related to biofilm formation in the heart valve vegetations. On this background, the present review will describe potentially novel non-antibiotic, antimicrobial approaches in IE, with special focus on anti-thrombotic strategies and hyperbaric oxygen therapy targeting the biofilm formation of infected heart valves caused by Staphylococcus aureus. The format is translational from preclinical models to actual clinical treatment strategies.